2021
DOI: 10.3390/jcm10143064
|View full text |Cite
|
Sign up to set email alerts
|

Modified Technique for Wirsung-Pancreatogastric Anastomosis after Pancreatoduodenectomy: A Single Center Experience and Systematic Review of the Literature

Abstract: Background: The mortality rate following pancreaticoduodenectomy (PD) has been decreasing over the past few years; nonetheless, the morbidity rate remains elevated. The most common complications after PD are post-operative pancreatic fistula (POPF) and delayed gastric emptying (DGE) syndrome. The issue as to which is the best reconstruction method for the treatment of the pancreatic remnant after PD is still a matter of debate. The aim of this study was to retrospectively analyze the morbidity rate in 100 cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Therefore, in this context, the question "pancreaticogastrostomy or pancreaticojejunostomy? ", first presented by Kausch and Whipple, still remains open today [8,30]. In this regard, a few reported meta-analyses and randomized trials have found that pancreaticogastrostomy might be better as it was associated with a smaller rate of pancreatic fistulas in the conducted studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in this context, the question "pancreaticogastrostomy or pancreaticojejunostomy? ", first presented by Kausch and Whipple, still remains open today [8,30]. In this regard, a few reported meta-analyses and randomized trials have found that pancreaticogastrostomy might be better as it was associated with a smaller rate of pancreatic fistulas in the conducted studies.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple advantages and disadvantages for both the pancreaticogastrostomy and pancreaticojejunostomy procedures have been communicated so far. A pancreaticogastrostomy is considered to be easier to perform (less technically demanding) than a pancreaticojejunostomy and its advantages include the following: the anatomic proximity, rich gastric vascularization, the gastric low pH preventing the activation of the pancreatic enzymes or inactivating them, absence of the enterokinase, and better postoperative control (endoscopy) with the possibility of gastric decompression and a putative lower risk of pancreatic fistula [2,8,30]. However, there are also disadvantages associated with such an anastomosis: difficult hemostasis of the gastric submucosa, a more difficult mobilization of the pancreas, increased risk of hemorrhage, postoperative delayed gastric emptying (due to gastroparesis and possible tensions on the anastomosis), and risk of pancreatic enzymes inactivation.…”
Section: Introductionmentioning
confidence: 99%
“…The overall rates of post-operative pancreatic fistula and delayed gastric emptying syndrome were low in this study [ 5 ]. They highlighted their results by comparing them with the available literature on wirsung-pancreato-gastro-anastomosis [ 5 ]. Furthermore, to reduce exocrine and endocrine complications, parenchymal-sparing pancreatic and duodenal resections have been considered for various benign or borderline malignant pancreatic tumors.…”
mentioning
confidence: 99%
“…For patients with a localized pancreatic tumor involving the periampullary region, pancreatoduodenectomy (PD) is the recommended surgery, although there is still no standard regarding the surgical reconstruction method. In the present Special Issue, Bizzoca et al found surgical morbidity and mortality rates of 26% and 6%, respectively, in a retrospective series of 100 patients treated with PD and reconstructed with wirsung-pancreato-gastro-anastomosis [ 5 ]. The overall rates of post-operative pancreatic fistula and delayed gastric emptying syndrome were low in this study [ 5 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation